Delayed Electroanatomic Mapping After Surgical Ablation for Persistent Atrial Fibrillation - Bulava, Alan; Mokracek, Ales; Kurfirst, Vojtech (The Annals of thoracic surgery, 2017)
BACKGROUND: Long-term efficacy of catheter-based treatment of persistent atrial fibrillation is unsatisfactory. Minimally invasive surgical ablation techniques have been developed recently but their true efficacy has never been systematically tested. METHODS: Seventy patients (median age 63.5 years) with persistent atrial fibrillation underwent epicardial thoracoscopic radiofrequency pulmonary vein (PV) isolation, linear ablation, Marshal ligament disruption, and exclusion of the left atrial appendage. The procedure was followed by electroanatomic mapping 2 to 3 months later. RESULTS: Only 76% of patients were in sinus rhythm at the beginning of electroanatomic mapping. Right PVs were found isolated in a higher proportion of patients compared with left PVs (75.7% versus 91.4%, p < 0.001). All four PVs and the left atrial posterior wall were isolated in 68.6% and 22.9% of patients, respectively. Most of the gaps around left PVs were localized in the superior and anterior quadrants, whereas in right PVs, the gaps were found predominantly on the roof and posterior wall. A typical site of reconduction on the inferior connecting line was the segment adjacent to the right inferior PV. No typical reconduction sites were found on the roof line, as 58.5% of patients required completion of the roof line along its full length. CONCLUSIONS: Epicardial PV isolation was successful in the majority of patients, but was underwhelming with regard to isolation of the left PVs. Effective epicardially placed linear lines were rare. Our results highlight the significant limitations associated with a single-stage surgical approach and underline the necessity for a two-staged hybrid approach in the treatment of persistent atrial fibrillation.
Keywords: senioři; elektrofyziologické techniky kardiologické; Time Factors; výsledek terapie; katetrizační ablace; Minimally Invasive Surgical Procedures; Middle Aged; mužské pohlaví; Adult; Follow-Up Studies; Electrophysiologic Techniques, Cardiac; následné studie; Catheter Ablation; ženské pohlaví; Humans; fibrilace síní; časové faktory; lidé středního věku; dospělí; miniinvazivní chirurgické výkony; Female; Aged; Atrial Fibrillation; Treatment Outcome; lidé; Male